2017
DOI: 10.1177/1934578x1701200215
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Content, Composition and Bioactivity of Juniper Species in Wyoming, United States

Abstract: The objective of this study was to evaluate variations in leaf essential oil (EO) content and composition of Juniperus species in the Bighorn Mountains {J. communis L. (common juniper), J. horizontalis Moench. (creeping juniper), and J. scopulorum Sarg. (Rocky Mountain juniper)} in Wyoming, USA. The EO was extracted via steam distillation of fresh leaves (needles). The EO composition of the three Juniper species varied widely. Overall, the essential oil content of fresh leaves was 1.0% (0.4-1.8% range in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 26 publications
2
23
1
Order By: Relevance
“…Present results were in accordance with similar studies since it was reported that monoterpene hydrocarbons [α-pinene (31.1%), β-myrcene (16.3%), sabinene (7.5%), limonene (6.2%) and β-pinene (3.7%)] were the major compounds identified in commercial JEO [47]. Similar results were also reported by Radoukova et al [48] and Zheljazkov et al [49]. It should be highlighted that variations in chemical profile of JEO could be related to genetic properties, geographical origin and climate conditions.…”
Section: Chemical Profile Of Jeosupporting
confidence: 93%
“…Present results were in accordance with similar studies since it was reported that monoterpene hydrocarbons [α-pinene (31.1%), β-myrcene (16.3%), sabinene (7.5%), limonene (6.2%) and β-pinene (3.7%)] were the major compounds identified in commercial JEO [47]. Similar results were also reported by Radoukova et al [48] and Zheljazkov et al [49]. It should be highlighted that variations in chemical profile of JEO could be related to genetic properties, geographical origin and climate conditions.…”
Section: Chemical Profile Of Jeosupporting
confidence: 93%
“…Lower values were reported in literature for the same or other juniper species. An EC 50 value of 34Á80 mg ml À1 was reported for the J. communis EO (H€ oferl et al 2014); the EOs of J. scopulorum and J. horizontalis were reported for their higher antioxidant capacity, evaluated with ORAC test, in comparison to J. communis (Zheljazkov et al 2017). Our results, obtained by DPPH test, showed that there are no significant difference in antioxidant activity between the tree oils.…”
Section: Discussionsupporting
confidence: 56%
“…Fresh leaves and branches from J. communis, J. horizontalis and J. scopulorum were collected in the Bighorn Mountains (Wyoming) in 2011. The EOs were obtained by steam distillation and the components were identified as described in Zheljazkov et al (2017).…”
Section: Essential Oilsmentioning
confidence: 99%
See 2 more Smart Citations